“IT WAS OUR LIVES, THAT WAS WHAT WE BELIEVED”: INDIGENOUS HISTORIES OF CATHOLICISM IN NORTHWEST SASKATCHEWAN - Fehr, Amanda Beth 1984- (2018)
This dissertation considers the variety of ways that Indigenous people in Patuanak (a Dene First Nation) and Ile-a-la-Crosse (a predominantly Cree/Metis village) in northwestern Saskatchewan have negotiated Catholicism from 1846 to the present, and the changing ways that they understand this history within their historical consciousness. This work contributes to a growing body of critical ethnohistory and Indigenous studies scholarship that focuses on Indigenous knowledge and suggests the complicated ways that Indigenous people have encountered colonial systems, while drawing attention to the need for scholars to make space for Indigenous Christianity beyond histories of conversion and the roles of the Christian Churches in the Canadian Indian Residential School system. This dissertation suggests the significance of Catholicism during the twentieth and early twenty-first centuries in northwestern Saskatchewan as necessary to understand processes and local experiences of colonialism, decolonization, and reconciliation. It considers how positionality and life history inform the variety of ways that people have historically negotiated their understandings of Indigeneity and Catholicism, and what it means to belong to a Catholic community. This work draws primarily on interviews that the author conducted with community members, and makes a methodological contribution in its effort to be more transparent about the research process throughout the written work. Chapters two and three focus on stories of Willow Heart, a Dene woman who helped the oblate priests and is considered to be a prophet. Stories of Willow Heart are used as an entrée to discuss local understandings of the Riel Resistance in 1885 and the 1906 Treaty Ten/Scrip Commission. Chapters four and five consider stories of Father Louis Moraud, an oblate priest in the region from 1916-1965 who is considered by many Elders as a local saint. In chapters six and seven, stories of decolonization within historically Catholic communities are discussed, focusing on ...